PENERAPAN METODE CERTAINTY FACTOR UNTUK MENGIDENTIFIKASI PENYEBAB CACAT PADA PRODUK PLASTIC INJECTION MOLDING DI PT TENMA CIKARANG INDONESIA - Fairujah Fairujah; Eko Martantoh (Journal of Innovation And Future Technology (IFTECH), 2023)
This study aims to develop and implement an expert system with the certainty factor method to identify the causes of defects in products produced by plastic injection molding machines at PT Tenma Cikarang Indonesia. This research begins by analyzing data on product defects recorded over a certain period to identify patterns of defects that frequently occur. Furthermore, an analysis of the factors that influence the occurrence of defects in plastic injection molding products is carried out. The certainty factor method was chosen as the basis for developing this expert system because this method is able to combine expert knowledge in the form of rules with the level of certainty for each of these parties. The process of developing this expert system involves the stages of modeling rules based on expert knowledge related to the causes of defects in plastic injection molding products. Furthermore, the implementation of these rules is carried out to calculate the level of certainty or certainty factor. The results of this study indicate that the developed expert system is successful in identifying the causes of defects in plastic injection molding products with a high degree of accuracy. This system can provide recommendations for appropriate corrective actions to address the type of identified defects. It is hoped that the application of this expert system at PT Tenma Cikarang Indonesia can increase production efficiency, reduce the number of product defects, and improve the quality of the products produced. Keyword: expert system, certainty factor, product defects, plastic injection molding